147k views
5 votes
Y=-3/4x+3 in standard form

User Ham
by
4.7k points

1 Answer

6 votes

Answer:


y=(-3)/(4) x+3 in standard form is 3x + 4y = 12

Solution:

Given that
y=(-3)/(4) x+3

To write a linear equation in standard form, follow the below steps:

The general form of equation is Ax + By = C


y=(-3)/(4) x+3

On cross-multiplication we get,


y = (-3x + 12)/(4)

Move 4 from denominator of right side to left side


4y = -3x + 12

On rearranging the terms we get

3x - 12 + 4y = 0

3x + 4y = 12

Thus the
y=(-3)/(4) x+3 in standard form is 3x + 4y = 12

User BastiBen
by
5.3k points